Efektivitas Psikoedukasi Pencegahan Kekerasan Sexual pada Anak di Pos PAUD Mawar Kelurahan Beru - Yohana Cassy Febrina; Sitti Anggraini (Mathematics Education Study Program, 2025)
The purpose of this study was to analyze how effective the psychoeducation program is in improving the knowledge, attitudes, and behavior of preschool children related to the prevention of sexual violence. This research method is a study with a pre-experimental one group pre-test-post-test design. This study compared the knowledge of preschool children about sexual violence before and after being given psychoeducation on the prevention of sexual violence. The sampling in this study used total sampling, meaning all children at the Mawar Paud Post in Beru Village, totaling 27 children. Based on the results of the paired sample t-test, the sig. (2 tailed) value was obtained at 0.000 <0.05. The results of this study showed that there was a significant difference in the increase between the pretest and posttest results. This shows that there is an influence of psychoeducation on the knowledge of preschool children regarding the prevention of sexual violence in preschool children at the Mawar Paud Post, Beru Village.